Surgical Management of Trigeminal Neuralgia in Elderly Patients Using a Small Retrosigmoidal Approach: Analysis of Efficacy and Safety - Martínez-Anda, Jaime Jesus; Barges-Coll, Juan; Ponce-Gomez, Juan Antonio; Perez-Pena, Nadia; Revuelta-Gutierrez, Rogelio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background Trigeminal neuralgia is one of the most common causes of facial pain with the highest incidence in individuals > 60 years old. Despite the proven efficacy and safety of microvascular decompression (MVD) for the treatment of trigeminal neuralgia, some physicians are reluctant to perform the procedure in elderly patients because of potential complications.Material and Methods In the present study, we analyze the outcome of MVDs performed over a 10-year period in elderly patients and compare the results with those obtained in younger patients. A total of 32% of the patients were ≥ 65 years of age at the time of diagnosis. All of the patients were treated via a small retrosigmoidal approach because of reluctance for medical treatment. Overall, 87% of the patients exhibited microvascular compression of the fifth nerve in the root entry zone and were treated using MVD; the remainder of the patients were treated using a trigeminal root compression technique when a vessel was not compressing the fifth nerve.Results After the procedure, 93% reported complete relief of pain with a recurrence rate of 10.8% over a mean time of 43 months. A total of 10% of the patients experienced severe complications related to the operation with no mortality.Conclusion MVD continues to be the procedure of choice for the treatment of trigeminal neuralgia in patients reluctant to medical treatment, including elderly patients because age is not a contraindication.
Keywords: trigeminal neuralgia; microvascular decompression; elderly